A Satellite-Based Model for Estimating Latent Heat Flux From Urban Vegetation - Smith, Ian A.; Winbourne, Joy B.; Tieskens, Koen F.; Jones, Taylor S.; Bromley, Fern L.; Li, Dan; Hutyra, Lucy R. (Frontiers in Ecology and Evolution, 2021)
The impacts of extreme heat events are amplified in cities due to unique urban thermal properties. Urban greenspace mitigates high temperatures through evapotranspiration and shading; however, quantification of vegetative cooling potential in cities is often limited to simple remote sensing greenness indices or sparse, in situ measurements. Here, we develop a spatially explicit, high-resolution model of urban latent heat flux from vegetation. The model iterates through three core equations that consider urban climatological and physiological characteristics, producing estimates of latent heat flux at 30-meter spatial resolution and hourly temporal resolution. We find strong agreement between field observations and model estimates of latent heat flux across a range of ecosystem types, including cities. This model introduces a valuable tool to quantify the spatial heterogeneity of vegetation cooling benefits across the complex landscape of cities at an adequate resolution to inform policies addressing the effects of extreme heat events.